Parameter Tuning Method for a Lattice Compensated Wireless Power Transfer System - Ebrahim Nasr Esfahani; Indranil Bhattacharya (Electricity)
This study presents a new charging system with lattice compensation for wireless power transfer (WPT) applications. A mathematical model is developed for the proposed system to accurately estimate power transfer capabilities. Furthermore, a linear programming algorithm is used to find the proper values for lattice compensation, which helps achieve high efficiency over a wide range of loads and zero voltage switching (ZVS) for the proposed system. The approach is validated through analysis, modeling, and simulation of a 3-kilowatt WPT system. Additionally, a 200-watt prototype with a 100 mm air gap was built and tested, showing an efficiency of 86.3% during charging. This method eliminates the need for an auxiliary DC–DC converter, ensuring efficient charging across various load conditions. The prototype’s performance closely matches the simulation results, indicating its potential for scaling up to electric vehicle (EV) battery charging applications.